The Influence of Earnings Quality Towards Investment Efficiency on Property and Real Estate Company Which Listed on Indonesia Stock Exchange Period 2011-2015 - admin, Ayu Trisnawati B42112012 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
The purpose of this study is to determine the effect of earnings quality which proxies by accruals quality towards investment efficiency whether partial or simultaneously significant. The object of the study is property and real estate company which listed in Indonesia Stock Exchange period 2011-2015 with amount of 35 companies. It is using simple linear regression analysis with classic assumption test and hypothesis test. The result shows that accruals quality has not simultaneously significant toward investment efficiency. Meanwhile, earnings quality has negative partially significant influence towards investment efficiency. Keywords: Earnings Quality (EQ), Accruals Quality (AQ), Investment Efficiency (IE